Combined Oral Contraceptive Use and the Risk of Cervical Cancer: Literature Review - Bovo, Adriane Cristina; Pedrão, Priscila Grecca; Guimarães, Yasmin Medeiros; Godoy, Luani Rezende; Resende, Júlio César Possati; Longatto-Filho, Adhemar; Reis, Ricardo dos (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2023)
Cervical cancer (CC) is caused by persistent infection of human papillomavirus of high oncogenic risk (hr-HPV); however, several cofactors are important in its carcinogenesis, such as smoking, multiparity, and prolonged use of oral hormonal contraceptives (COCs). Worldwide, 16% of women use COCs, whereas in Brazil this rate is of ∼ 30%. The safety and adverse effects of COCs are widely discussed in the literature, including the increase in carcinogenic risk. Due to the existence of several drugs, combinations, and dosages of COCs, it is hard to have uniform information in epidemiological studies. Our objective was to perform a narrative review on the role of COCs use in the carcinogenesis of cervical cancer. Several populational studies have suggested an increase in the incidence of cervical cancer for those who have used COCs for > 5 years, but other available studies reach controversial and contradictory results regarding the action of COCs in the development of CC.
Keywords: Oral hormonal contraceptives; Cervical cancer; HPV